Nanopartículas de Pt suportadas em Al2O3 e CeO2-Al2O3: síntese, caracterização e propriedades catalíticas para reforma do metano - Prieto, Paulo Juliano dos Santos (2007)
A new method to prepare Pt nanoparticles (NPs) dispersed on Al2O3 and CeO2-Al2O3 is described in this work. The Pt-NPs were used to prepare CeO2-Al2O3-supported Pt nanocatalysts (Pt-NPs/Al2O3 and Pt-NPs/CeO2-Al2O3). The catalysts were characterized by BET surface area (SBET), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) reaction of dehydrogenation of cyclohexane to measure Pt dispersion and transmission electronic microscopy (MET). The Pt-NPs were obtained from solution of [PtCl6]2-, poly(Nvinyl- 2-pyrolidone) (PVP) and methanol. The Al2O3 and CeO2-Al2O3 supports were obtained by sol-gel methods. The Pt-NPs/Al2O3 and Pt-NPs/CeO2-Al2O3 catalysts were obtained by addition of Pt-NPs sol during sol-gel synthesis Al2O3 and CeO2-Al2O3. TEM analysis show that the synthesis of the Pt-NPs resulted in particles with average size of 3.2 nm and the results of TEM of the catalysts indicate that Pt particles, finely dispersed on the support occupying probably the interior of the pores of the support. The comparison between FTIR-CO results of Pt-NPs/Al2O3 and Pt-NPs/CeO2-Al2O3 catalysts indicated that the particles in the different catalysts show the same electronic density superficial and that there is a geometric modification on the surface of the particles of the Pt- NPs/CeO2-Al2O3 catalyst provoked by presence of CeOx on the surface of particles. The nanocatalysts Pt-NPs/Al2O3 and Pt-NPs/CeO2-Al2O3 exhibited a high catalytic activity and stability for the steam reforming of methane and for the partial oxidation of methane. The CH4 turnover rate of Pt-NPs/CeO2-Al2O3 catalysts for the steam reforming of methane is around two orders of magnitude higher compared to that of Pt-NPs/Al2O3 catalyst. The high activity for Ce-contaning catalysts is assigned to higher accessibility of the Pt sites to CH4. The high stability of Pt-NPs/Al2O3 and Pt-NPs/CeO2-Al2O3 nanocatalysts in partial oxidation of methane is assigned to the high contact metal-support, which can be caused by preparation method that improves the accessibility of methane to Pt sites.